THE THOBE DRESS AS A NEW POLITICAL MOVEMENT AND FORM OF PALESTINIAN RESISTANCE - Anna Zakiah Derajat; Toni Kurniawan (CMES (Center of Middle Eastern Studies), 2023)
This research aims to analyze the issues of the new political movement and forms of Palestinian resistance through socio-cultural movements from the perspective of Sidney G. Tarrow. This resistance is reflected in the use of the thobe dress at the national and global levels. The movement began with posting photos of Palestinian women wearing thobes, leading to actions such as Rashida Tlaib, a member of the U.S. Congress, wearing a thobe during her inauguration. The research uses a descriptive analysis method with a literature review technique that focuses on interpreting the use as a social movement. The results show that the phenomenon of thobe use represents the resistance politics of Palestinian society and other supportive communities in confronting Zionist groups and elite factions that have marginalized Palestine.